Exchange Rate Elasticities of International Tourism and the Role of Dominant Currency Pricing - Ding, Ding (IMF Working Papers; Working Paper ;, 2022)
We estimate a variety of exchange rate elasticities of international tourism. We show that, in addition to the bilateral exchange rate between the tourism origin and destination countries, the exchange rate vis-a-vis the US dollar is also an important driver of tourism flows and pricing. The effect of US dollar pricing is stronger for tourism destination countries with higher dollar borrowing, indicating a complementarity between dominant currency pricing and financing. Country-specific dominant currencies (CSDCs) play only a minor role for the average country, but are important for tourism-dependent countries and those with a high concentration of tourists. The importance of the dollar exchange rate represents a strong piece of evidence of dominant currency pricing (DCP) in the international trade of services and suggests that the benefits of exchange rate flexibility for tourism-dependent countries may be weaker than previously thought.